Teaching an Old Dog New Tricks: Using the Dividend Growth Model in Financial Planning - Brooks,Raymond; Yang,Jimmy (Journal of Economics and Finance Education, 2007)
The Dividend Growth Model is a standard pedagogical tool in pricing stocks where the dividend grows at a constant rate. However, few dividend policies conform to this restrictive pattern and therefore the model is often quickly discarded in finance classes. The constant growth assumption of a cash flow stream fits well with other financial problems such as saving for a college education or contributions to a pension plan. This paper presents a couple of applications for the Dividend Growth Model plus an extension to the model and belies the adage: you can’t teach an old dog new tricks.
Keywords: Finance